Sentiment Analysis of Qardh Hasan Scheme - Maulida, Syahdatul (Tamkin Journal, 2023)
This study aims to assess sentiments related to qardh hasan in scientific publications published in the period 2011 to 2023. The research method used is sentiment analysis by utilizing SentiStrength software, which serves to categorize sentiment into three levels, namely positive, neutral, and negative. The data used comes from scientific publications indexed in the Scopus database. The findings showed the dominance of neutral sentiment in scientific publications at 43%, followed by positive sentiment at 33%, and negative sentiment at 24%. In addition, the study revealed periodic fluctuations in the number of sentiments related to qardh hasan in scholarly publications, with 2023 showing the highest number of sentiments. The implications of the results include contributing to the literature on qardh hasan as well as highlighting the impact and challenges in the development of qardh hasan in different parts of the world.